Contribuições Da Referenciação Para O Ensino-Aprendizagem De Língua Portuguesa, Com Ênfase Na Natureza Argumentativa Da Linguagem (PERcursos Linguísticos, 2021)
The broader purpose of this article is to suggest a reflection about the relation between text linguistics and Portuguese teaching and learning. It puts as a starting point the postulate assumed by text linguistics that takes place in Brazil nowadays, which comprehends argumentation as an inherent process of any language, once all texts have a direction, posed by locutors, to change, at some level, the interlocutor’s state of being (CAVALCANTE at al., 2020). Based on this, we elect the process of referentiation as the strategy to be explored in pedagogical practices, proposing an analysis of two activities in which the building of coherence depends on the argumentative perception of the referents. We believe that these activities show the promotion of effective learning, in both the levels of argumentative aim and argumentative dimension (AMOSSY, 2011). Furthermore, these activities, taking account the apprentice action over texts, instead of putting attention only to the merely expositive view of mechanisms of referential cohesion, aloud the renovation (urgent, in our opinion) of the pedagogical work with textualization strategies.